Edukasi Bahaya Jajanan Sembarangan - Dwi Helynarti Syurandhari; Elyana Mafticha; Asih Media Yuniarti (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2026)
Children's health is one of the important aspects in the development of quality human resources. One of the main factors affecting children's health is the habit of choosing healthy snacks. However, snacks sold around schools often contain harmful substances that can have a negative impact on children's health. Therefore, this community service activity aims to enhance students' knowledge about choosing healthy snacks through methods such as educational lectures, group discussions, educational games, and direct demonstrations. The pre-test results show that most students were in the Satisfactory and Poor categories, while the post-test results show significant improvement, with almost all students, 28 out of 30 (93.33%), achieving the Good category. This indicates that the educational methods used were highly effective in improving students' understanding of how to select healthy snacks. Based on active and experiential learning theories, the methods applied in this activity have proven successful in motivating students to make better choices regarding the snacks they consume. Overall, this activity can be used as a model in developing nutritional education for children in schools across Indonesia